Niqabi Women and Catcalling: A Phenomenological Study of Sexual Harassment Towards Niqabi in Surakarta - Dinanti, Dinda Angela; Sunesti, Yuyun (DINIKA : Academic Journal of Islamic Studies, 2023)
Catcalling is a form of sexual harassment involving the use of indecent language towards victims, typically women. While it is commonly assumed that catcalling targets female victims based on the exposure of certain body parts, it is noteworthy that women, even those who wear modest clothing or even a niqab, also experience catcalling. This article delves into the phenomenon of catcalling as experienced by niqabi. Data for this study were generated through field research conducted in Surakarta, utilizing in-depth interviews with ten niqabis of various ages and educational backgrounds. Employing a phenomenological approach and applying Blumer's theory of symbolic interactionism, the study reveals diverse causes, forms, and impacts of catcalling on women who wear the niqab. Despite facing catcalling, these niqabis employ both active and passive strategies to protect themselves. This research sheds light on the multifaceted aspects of catcalling experienced by women who choose to wear the niqab. This article contributes to the discussion on the issue of sexual harassment against women and the study of the dynamics of niqabi women.